Flow as a positive state: antecedents and outcomes of flow states - Van Ittersum, Kyle W. (Kansas State University, 2013)
The field of Industrial/Organizational Psychology has begun to incorporate elements from the growing field of Positive Psychology which has been manifest in Positive Organizational Scholarship (POS) and Positive Organizational Behavior (POB). This study examined two POB constructs, Psychological Capital (PsyCap) and Flow in a lab-based virtual-world simulation while utilizing Fredrickson’s (2001) broaden-and-build theory of positive emotions. It was hypothesized that PsyCap would predict flow experiences and that those flow experiences would predict several outcomes, namely performance, affect, and resilience. It was found that individuals higher in Psychological Capital tended to experience more flow in a flow inducing task. During that task, individuals in flow performed better and experienced more positive affect than individuals who experienced lower levels of flow. Additionally, flow in that task was able to predict performance, affect, and resilience in a later, overly challenging task. Implications for these findings are discussed as well as limitations and future directions.
Keywords: Flow; Psychological Capital; Resilience; Positive States; Psychology (0621)